Para atuar com a comunidade: estudo sobre a relação entre participação comunitária e estratégia de saúde da família do SUS no Bairro Terrenos Novos em Sobral, Ceará - Nepomuceno, Léo Barbosa (2009)
The research part of the finding, based in several studies, that the Family Health Care Strategy (ESF), established as Primary Health in the National Public Health (SUS) in Brazil, has not encouraged a significant community participation. Supports the idea that community participation is essential to the advance of ESF work, and bring elements to enrich the debate on the theme of social participation in SUS. Studies the relationship between the Family Health Care Strategy (ESF) and community participation in Terrenos Novos neighborhood, in Sobral-CE. Analyzes the understanding of the group of users and professionals in the ESF about community participation, the ESF work and the relationship between them; evaluates community participation, the work of the ESF and the relationship between those in the community studied, presents and create proposals, with residents and professionals of the municipal health system of Sobral, to strengthen community participation and the ESF. Its theoretical mark is the Community Psychology and its interfaces with the Social Psychology of Health, Community Health and Public Health. Consists an exploratory and field research of qualitative approach. A thematic analysis is performed as the main methodological strategy, like a technique of content analysis of empirical material produced in the culture circles performed with the group of participants. As an additional methodological strategy, analyze the field notes taken and materials in work done by the researcher in the place. The search results are divided into three main themes: community participation, the ESF and the relationship between them. The theme of the Community highlights concepts of community participation related to ideas of solidarity with the other, an involvement and commitment to what is common, a need to collectively seek improvements to the neighborhood. The evaluation of community participation in Terrenos Novos neighborhood points to a "disenchantment" and decline of this process in the place. The theme of the ESF's work points to several conceptions, ranging from visions impregnated with the ideology of the biomedical model to more differentiated views that argue defends an attention focused on the family health and in tune with the reality of the territory-community. The evaluation of the work of the CSF studied mainly points to weaknesses in the health care. The discussion of the topic of the relationship between community participation and ESF highlights the importance of this relationship to the advancement of health work and the need to improve the relationship between these processes. Several relevant factors were identified in the relationship between ESF and the Community, among them: the professional commitment, the ability of social reading of the professionals, the need to resize the work process for health promotion; the power relationship between professional and user, the ability to practice the co-responsibility with the user, and need to create permanent spaces of dialogue between the CSF and the community.